Changes in lung function in European adults born between 1884 and 1996 and implications for the diagnosis of lung disease: a cross-sectional analysis of ten population-based studies. Issue 1 (January 2022) - Allinson, James P; Afzal, Shoaib; Çolak, Yunus; Jarvis, Debbie; Backman, Helena; van den Berge, Maarten; Boezen, H Marike; Breyer, Marie-Kathrin; Breyer-Kohansal, Robab; Brusselle, Guy; Burghuber, Otto C; Faner, Rosa; et al.
Summary: Background: During the past century, socioeconomic and scientific advances have resulted in changes in the health and physique of European populations. Accompanying improvements in lung function, if unrecognised, could result in the misclassification of lung function measurements and misdiagnosis of lung diseases. We therefore investigated changes in population lung function with birth year across the past century, accounting for increasing population height, and examined how such changes might influence the interpretation of lung function measurements. Methods: In our analyses of cross-sectional data from ten European population-based studies, we included individuals aged 20–94 years who were born between 1884 and 1996, regardless of previous respiratory diagnoses or symptoms. FEV1, forced vital capacity (FVC), height, weight, and smoking behaviour were measured between 1965 and 2016. We used meta-regression to investigate how FEV1 and FVC (adjusting for age, study, height, sex, smoking status, smoking pack-years, and weight) and the FEV1 /FVC ratio (adjusting for age, study, sex, and smoking status) changed with birth year. Using estimates from these models, we graphically explored how mean lung function values would be expected to progressively deviate from predicted values. To substantiate our findings, we used linear regression to investigate how the FEV1 and FVC values predicted by 32 reference equations published between 1961 and 2015 changed with estimated birth year. Findings: Across the ten included studies, we included 243 465 European participants (mean age 51·4 years, 95% CI 51·4–51·5) in our analysis, of whom 136 275 (56·0%) were female and 107 190 (44·0%) were male. After full adjustment, FEV1 increased by 4·8 mL/birth year (95% CI 2·6–7·0; p<0·0001) and FVC increased by 8·8 mL/birth year (5·7–12·0; p<0·0001). Birth year-related increases in the FEV1 and FVC values predicted by published reference equations corroborated these findings. This height-independent increase in FEV1 and FVC across the last century will have caused mean population values to progressively exceed previously predicted values. However, the population mean adjusted FEV1 /FVC ratio decreased by 0·11 per 100 birth years (95% CI 0·09–0·14; p<0·0001). Interpretation: If current diagnostic criteria remain unchanged, the identified shifts in European values will allow the easier fulfilment of diagnostic criteria for lung diseases such as chronic obstructive pulmonary disease, but the systematic underestimation of lung disease severity. Funding: The European Respiratory Society, AstraZeneca, Chiesi Farmaceutici, GlaxoSmithKline, Menarini, and Sanofi-Genzyme.